STUDY OF MAKING BLACK RICE COOKIES - Ni Luh Gede Sri Artini; Ni Putu Agustini; Ni Nyoman Astika Dewi (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
Black Rice is one of the rice which is high in anthocyanin and fiber levels. Black rice can be processed into various kinds of processed foods to add nutritional value. Cookies are processed and cooked flour products made from a mixture of margarine, eggs and milk powder with or without the addition of other food ingredients and food ingredients that are allowed. The substitution of wheat flour with black rice flour can add to the nutritional value of cookies. This study aims to determine organoleptic characteristics including taste, aroma, color, texture, overall acceptance and taste quality and texture quality in black rice cookies, to determine the best anthocyanin level for black rice cookies, and calculate the nutrient content produced in 1 portion the best black rice cookies. This study uses experimental methods with a type of Randomized Block Design (RBD). There are 4 treatments with substitution of wheat flour 90%, 85%, 80%, 75% and black rice flour 10%, 15%, 20%, 25%. Based on the results of the Variety Investigation Test, black rice cookies which are substituted with 90% wheat flour with 10% black rice flour with taste characteristics, aroma, color, texture, overall acceptance and taste quality and texture quality have a significant effect. In 100 grams of black rice cookies containing anthocyanin at 0.0762 mg / 100g. Keywords: Black rice, cookies, anthocyanin.